Efficacy of taxanes rechallenge in first-line treatment of early metastatic relapse of patients with HER2-negative breast cancer previously treated with a (neo)adjuvant taxanes regimen: A multicentre retrospective observational study. (October 2022) - Vasseur, Antoine; Carton, Matthieu; Guiu, Severine; Augereau, Paule; Uwer, Lionel; Mouret-Reynier, Marie-Ange; Levy, Christelle; Eymard, Jean-Christophe; Ferrero, Jean-Marc; Leheurteur, Marianne; Goncalves, Anthony; Robert, Marie; et al.
Abstract: Background: Taxanes are one of the most effective chemotherapies (CT) in breast cancer (BC), but the efficacy of taxanes rechallenge in early metastatic relapse has been poorly studied in patients previously treated by taxanes in the (neo)adjuvant setting. Our study aimed to analyse the efficacy of taxane rechallenge in case of early metastatic relapse in a multicentre retrospective observational study compared with other chemotherapies. Methods: We analysed the French national ESME metastatic BC (MBC) database and selected HER2- MBC patients who received CT in first-line treatment for a metastatic relapse occurring 3–24 months after previous (neo)adjuvant taxanes treatment. Results: Of 23, 501 female patients with MBC in ESME, 1057 met the selection criteria. 58.4% received a taxane-based regimen (75.4% concomitant bevacizumab) and 41.6% received other CT. In hormone-receptor positive (HR+)/HER2- MBC, multivariate analysis showed no difference in OS between taxanes without bevacizumab compared to other CT (HZR = 1.3 [0.97; 1.74], but taxanes was significantly associated with worse PFS (HZR = 1.48 [1.14; 1.93]). In TNBC, taxanes without bevacizumab and carboplatin/gemcitabine were not superior to other CT for OS (HZR = 1.07 [0.79; 1.44] and HZR = 0.81 [0.58; 1.13], respectively), while for PFS, taxanes was inferior (HZR = 1.33 [1.06–1.67]) and carboplatin plus gemcitabine was superior to other CT (HZR = 0.63 [0.46; 0.87]). For both subtypes, the worse outcome observed with paclitaxel was no longer observed with the addition of bevacizumab. Conclusions: With the limitation of retrospective design, taxanes rechallenge in early metastatic relapse of BC may result in a worse PFS in TNBC and HR+/HER2- MBC, which was not observed with the addition of bevacizumab. Highlights: Patients with HER2-advanced breast cancer (ABC) have often previously received taxanes in the (neo)adjuvant setting. Current guidelines suggest a rechallenge by taxanes in ABC with DFI≥12 months, few data are available for DFI ≤24 months. Taxane rechallenge in early metastatic relapse of BC (DFI ≤24 months) may result in a worse PFS in TNBC and HR+/HER2- ABC. In TNBC, the addition of bevacizumab to taxanes improves PFS and OS for DFI ≤24 months.